Monitoring fibrous scaffold guidance of three-dimensional collagen organisation using minimally-invasive second harmonic generation. - Robin M Delaine-Smith; Nicola H Green; Stephen J Matcher; Sheila MacNeil; Gwendolen C Reilly (PLoS ONE)
The biological and mechanical function of connective tissues is largely determined by controlled cellular alignment and therefore it seems appropriate that tissue-engineered constructs should be architecturally similar to the in vivo tissue targeted for repair or replacement. Collagen organisation dictates the tensile properties of most tissues and so monitoring the deposition of cell-secreted collagen as the construct develops is essential for understanding tissue formation. In this study, electrospun fibres with a random or high degree of orientation, mimicking two types of tissue architecture found in the body, were used to culture human fibroblasts for controlling cell alignment. The minimally-invasive technique of second harmonic generation was used with the aim of monitoring and profiling the deposition and organisation of collagen at different construct depths over time while construct mechanical properties were also determined over the culture period. It was seen that scaffold fibre organisation affected cell migration and orientation up to 21 days which in turn had an effect on collagen organisation. Collagen in random fibrous constructs was deposited in alternating configurations at different depths however a high degree of organisation was observed throughout aligned fibrous constructs orientated in the scaffold fibre direction. Three-dimensional second harmonic generation images showed that deposited collagen was more uniformly distributed in random constructs but aligned constructs were more organised and had higher intensities. The tensile properties of all constructs increased with increasing collagen deposition and were ultimately dictated by collagen organisation. This study highlights the importance of scaffold architecture for controlling the development of well-organised tissue engineered constructs and the usefulness of second harmonic generation imaging for monitoring collagen maturation in a minimally invasive manner.